In vitro study of antioxidant and antibacterial properties of Phyllanthaceae and Rubiaceae plant families from Simeuleu Island, Aceh, Indonesia - Marlin Megalestin Raunsai; Ahmad Fathoni; Andria Agusta (Pharmaciana, 2022)
Plants are still the preferred solution to solve several of the main problems the world is facing today, such as antibiotic resistance and free radicals. The plant chemical compounds have the potential as antibacterial and antioxidant agents. Therefore, four plants representing Phyllantaceae family (Glochidion varians Miq., Glochidion zeylanicum (Gaertn.) A.Juss) and two plants from Rubiaceae family (Uncaria lanosa var. glabrata, and Uncaria cordata (Lour.) Merr.)Â  were collected from Simeulue island, Aceh. We obtained 32 extracts from several plants with various solvents, such as hexane, dichloromethane, ethyl acetate, and methanol. The methods applied to investigate antibacterial activities were Thin Layer Chromatography (TLC) and Minimum Inhibitory Concentration (MIC). Meanwhile, TLC and Microdilution Assay were utilized to analyze antioxidant capacity against 1,1-diphenyl-2-picrylhydrazyl (DPPH). The result of antibacterial activity shows 32 extracts displayed very strong to weak activity against Staphylococcus aureus and Escherichia coli. Among all extracts, methanol extracts of G. varians (stem and leaf), methanol extracts of G. zeylanicum (stem and leaf), methanol and ethyl acetate extracts of U. cordata (leaf), and ethyl acetate extract of G. varians (leaf) indicate potent antioxidant activity with the range of antioxidant activity index (AAI) values of 2.16 -11.73. Furthermore, all extracts exhibit moderate to weak antibacterial evaluation. The methanol extract of G. varians stem has the highest MIC value of 128 µg/ml against S. aureus. The methanol extracts of G. varians stem and leaf and methanol extract of G. zeylanicum leaf against E. coli have MIC value of 256 µg/ml, whereas other extracts have >256 µg/ml MIC value. To sum up, four plants from Phylantaceae and Rubiaceae families have the potential to be expanded as antioxidant agents rather than antibacterial agents.